POWER RELATIONSHIP IN NATURAL RESOURCES MANAGEMENT OF NAN STAGE SINCE 1855-1932 - Jedeetha, Nitwadee; Kunphoommarl, Montri (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
This research is historical research using documents from the National Archives, research documents, and the recollections of those who were present at various events. This study focuses on the power relations that were negotiated between Siam, England, and France as the colonization of Southeast Asia during the 19th century resulted in many countries becoming Western colonies. Even the prosperous and dominant Empire of Siam was threatened by the Western powers. The Empire of Siam had the advantage of numerous vassal states that could be negotiated with to preserve the independence of the majority of the empire’s territory. To the north, the Lanna Empire shared its border with British-controlled Burma, while the important city of Luang Prabang was a French colonial city. At that time, the important city that was on the border with the two colonial rulers was the Nan State. Although the colonial influence of both nations expanded into Nan after Chiang Mai, the British teak concession was closely watched by the Siamese government from Bangkok. Moreover, Nan State had a border with Luang Prabang that had a disputed boundary over its rock salt resources, although Siam had learned lessons in forestry concessions from western Lanna. As the scope of concessions expands to the east, power cannot be avoided. The advantage of expanding influence allowed Siam to correct the same from other cities. There were resources in the area of Nan State such as forests, rock salt, or even resource areas as a condition for negotiations with the two superpowers, especially the management of forest concessions which were an important resource. As a result, Siam continued to maintain its own power status like other countries and was able to retain power that changed from Nan State to Nan Province of Thailand today.